Estimasi Tekanan Atrium Kanan Dengan Rasio Gelombang E/Ea Katup Trikuspid - Yasmina Hanifah; Amiliana M Soesanto; Ismoyo Sunu; Ganesja M Harimurti (The Indonesian Heart Association, 2010)
Background. Right atrial pressure is one of hemodynamic parameter that can guide therapy for patients in intensive care unit. Right atrial pressure is also needed for calculation of other hemodynamic parameter such as pulmonary pressure and systemic vascular resistance. Estimation of right atrial pressure using E/Ea ratio is not much studied until now. There were only three studies with different result. This study objective is therefore to asses the correlation and agreement of estimation right atrial pressure by using ratio E wave (spectral doppler) and Ea wave (tissue doppler imaging) from tricuspid valve. Methods.This is a diagnostic test with cross sectional design study in patients in Cardiovascular Care Unit (CVCU) who had been inserted central venous pressure line (CVP line). E wave was taken from tricuspid inflow with pulsed wave spectral doppler and Ea wave was taken from the lateral tricuspid annulus with tissue doppler imagingat at early diastolic filling. Correlation analysis was performed to assess the correlation of E/Ea ratio with right atrial pressure from CVP line. The result of E/Ea ratio liner regrresion is analyzed with bland altman plot to asses agreement between E/Ea ratio and invasive methods of CVP line. Data was analyzed using SPSS 15.0.Results.There were 50 from 16 sample. As many as 20 data was also also measured by second observer for interobserver variability. There was a good precision for inter and intraobserver with ICC > 0,8. There was good correlation between E/Ea ratio with right atrial pressure, r = 0.728, p < 0,001. Cut off point E/Ea >3,95 could predict right atrial pressure = 10 mmHg (sensitvity 73,1% and specificity 70,8% and positive predictive value 73% and negative predictive value 73,9%). The agreement between E/Ea ratio and CVP line for measuring right atrial prssure was poor, with Intra-class Correlation(ICC) 24% and percentage error more than 30%. Based on this agreement right atrial pressure estimated by E/Ea ratio could have difference as much as 0,01 +3,53 mmHg. Conclusion.There were good correlation but poor agreeement for right atrial pressure estimation by using E/Ea ratio.